2001
DOI: 10.1021/np0100690
|View full text |Cite
|
Sign up to set email alerts
|

Tetillapyrone and Nortetillapyrone, Two Unusual Hydroxypyran-2-ones from the Marine Sponge Tetilla japonica

Abstract: Extraction of the marine sponge Tetilla japonica from the Bay of Thailand furnished tetillapyrone and nortetillapyrone, two unusual tetrahydrofurylhydroxypyran-2-ones, whose structures were established by NMR spectrometry and an X-ray analysis of tetillapyrone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…It was crystallized from acetone as colorless needles with mp 192 -1938C and ½a 27 D þ 27.0 (c 0.1, acetone); NMR and MS spectral data of compound 3 were found completely identical to the data reported in the literature [3].…”
Section: Compoundsupporting
confidence: 61%
See 1 more Smart Citation
“…It was crystallized from acetone as colorless needles with mp 192 -1938C and ½a 27 D þ 27.0 (c 0.1, acetone); NMR and MS spectral data of compound 3 were found completely identical to the data reported in the literature [3].…”
Section: Compoundsupporting
confidence: 61%
“…Both the extracts were combined after concentration and subjected to solvent partition to afford hexane, chloroform, and n-butanol-soluble and -insoluble fractions. The n-butanol-soluble fraction was chromatographed over silica gel column to give a mixture of two new ceramides 1, 2 and a pyrone previously reported [3] from the sponge Tetilla. The mixture of ceramides was rechromatographed over silica gel (100-200 mesh) to give pure compounds 1 and 2 as white amorphous powders.…”
Section: Resultsmentioning
confidence: 99%
“…All of these evidences, combined with the new isolation of more quantities of tetillapyrone and nortetillapyrone from the marine sponges H. cymaemormis and H. baeri, have led us to re-examine their structures by careful analysis of the HMBC spectra of both compounds. The structure of tetillapyrone (5), previously proposed by us [11], was based on the fact that one carbon signal was missing in the 13 C NMR spectrum and thus the carbon signal at δ109.45 was attributed to C-3 and C-5 of the pyrone ring. As the protons of the methyl group (δ1.76s) on C-3 of the pyrone ring and the hydroxyl proton at δ11.28s, showed crosspeaks with the carbon at δ109.45, we have concluded that the hydroxyl group was on C-6.…”
Section: Resultsmentioning
confidence: 93%
“…We have previously reported isolation of tetillapyrone (5) and nortetillapyrone (8) from the marine sponge Tetilla japonica, collected from the Gulf of Thailand [11]. Though the structures of both compounds were established by 1 H, 13 CNMR, COSY, NOESY, HETCOR, HMBC and HRMS as well as by X-ray analysis in the case of tetillapyrone (5), there were still some uncertainties with respect to the pyrone moiety.…”
Section: Resultsmentioning
confidence: 99%
“…The α-pyrones, such as pestalopyrone, [8] the verrucosapyrones, [12] LL-P880α, [15] and LL-P880β, [24] usually possess C-6 attached side-chains of three to five carbon atoms in length. Scirpyrone A (1) is structurally related to cladobotrin I (11) [25] and tetillapyrone (12), [26] a relatively rare class of α-pyrones with the furylpyranone skeleton, but dif-fers significantly in having a γ-lactone ring joined to the pyrone moiety through C-6 and C-7, rather than a C-5-C-7 connected furan or tetrahydrofuran in known compounds, representing the first described 6-(5-oxotetrahydrofuran-2yl)-2H-pyran-2-one. Scirpyrone B (2), however, differs from the known α-pyrones in possessing a butyl group attached to C-7, and is presumably the ring-opened product of 1.…”
Section: Discussionmentioning
confidence: 99%